Głowiński: tożsamość prozą (od początku) - Kuczyńska-Koschany, Katarzyna (Poznańskie Studia Polonistyczne. Seria Literacka, 2013)
The article is an attempt to reach the first statements and texts by Michał Głowiński, relating to Jewish identity in Poland, the condition of a child of the Holocaust, the trauma of a Holocaust survivor, and the situation of an intelectual. The author of the article tries to demonstrate continuity of all creative gestures, from the frist writings and statements, signed with pseudonyms, through Czarne sezony [The Black Seasons] and their continuations, to the autobiographical Kręgi obcości [Circles of strangeness]; the continuity is seen in the perspective of identity. The author is also interested, in the given subject scope, in Głowiński’s spatial obsessions (especially claustrophobia and phantasmagoria). The stake of literary “self-therapy” is in the most crucial things: truth of oneself, memory, self-identification.